Human resource development practices as determinant of HRD climate and quality orientation - Hassan, Arif; Hashim, Junaidah; Ismail, Ahmad Zaki (Emerald Group Publishing Limited, 2006)
Purpose – The aim of the study was to measure employees’ perception of human resource development (HRD) practices, to explore whether ISO certification leads to any improvements in HRD system, and to examine the role of HRD practices on employees’ development climate and quality orientation in the organization. Design/methodology/approach – A total of 239 employees belonging to eight organizations (four of them ISO certified) responded to a questionnaire which measured the following variables: career system, work planning system, development system, self renewal system, and HRD system. Findings – Results indicated large inter-organizational differences in HRD practices. In general,however, employees’ ratings were moderate. ISO certified companies, compared to others, obtained higher means on some HRD variables. Organizations with better learning, training and development systems, reward and recognition, and information systems promoted human resource development climate. Quality orientation was predicted by career planning, performance guidance and development, role efficacy, and reward and recognition systems. Research limitations/implications – Comparison between ISO and non-ISO certified companies did yield some significant differences, yet it was difficult to conclude that the differences were due to ISO certification alone as organizations in the sample were not matched. Practical implications – The findings can be used by HR practitioners and scholars in building management concerns and advocacy for better HRD systems and practices. Originality/value – Very little empirical knowledge is available on this subject from transitional economies like Malaysia. The study makes a modest attempt in that direction.